PENGGUNAAN GAYA BAHASA DALAM TUGAS PEMBELAJARAN KETERAMPILAN MENULIS CERITA FANTASI SISWA KELAS VII G SMPN 6 KOTA JAMBI TAHUN AJARAN 2021/2022 - Firman Tara; Nike Nurjayanti (Universitas Batanghari, 2022)
This study aims to describe the use of language style in learning assignments for writing fantasy story of grade VII G students of SMPN 6 Jambi City The 2021/2022. It is interesting to examine the ability to use student language styles in writing fantasy stories because with the style of fantasy stories, it will be interesting writing. Meanwhile, the conditions from the observations illustrate that students predominantly only use a certain style of language in writing literary works. This research uses qualitative descriptive method. This research data is in the form of a fantasy story writing assignment for grade VII G students of SMPN 6 Jambi City for the 2021/2022 which is related to the use of personification language styles, the use of metaphorical language styles, and the use of simile language styles. The author's qualitative descriptive research method is used as a way to describe the use of language style in the learning task of this student's fantasy story writing skills. The results of this study illustrate that students are more dominant in using personification language styles in the task of writing fantasy stories than using metaphorical language styles and simile language styles. Therefore, from the results of this study, the author hopes that in learning teachers will focus more on using various language styles to make students skilled in writing fantasy stories.